The Creative Process of Musical Composition “Sebatas Mimpi” Through the Exploration of Melodic Variations - Dimas Ilham Wibisono (Universitas Negeri Surabaya, 2026)
The song titled “The Composition of ‘Sebatas Mimpi’ Through the Exploration of Melodic Variations” tells the story of a person’s heartfelt emotions as they accept with an open heart the reality that the one they love does not love them in return. The purpose of this work is to serve as a new reference for other composers regarding orchestration techniques in programmatic music, particularly songs themed around disappointment and sadness; to serve as a reference for creating similar works; and to offer a musical composition that can be performed in concerts as a contribution to the development of music in the present and future. The result of this composition is a piece totaling 98 measures in the key of A. It features various sections, including choruses, verses, and others, and incorporates modulations throughout. It is performed in a chamber music format, with a double quartet augmented by piano and double bass. The compositional technique employed in this piece utilizes homophonic texture. During the creation of this piece, the researcher drew significant inspiration and ideas from Yovie Widianto.